The approach to the environmental issues in postgraduate nursing in Brazil - Camila Henriques Nunes; Mario Sergio Michaliszyn; Eduardo Shimoda; Karla Rangel Ribeiro; Ronilson Gonçalves Rocha
ABSTRACT Objectives: to analyze the insertion of environmental issues in the postgraduate stricto sensu in nursing in Brazil. Methods: quali-quantitative research, of exploratory approach, with documental research in the Sucupira Platform and in sites of the 112 courses stricto sensu in Nursing in Brazil, in 2018. We analyzed the curricular matrixes; course menus; teaching profile; dissertations and thesis (2004-2016); and bibliographic productions of the four-year evaluation 2013-2016. The analysis of quantitative data was performed by statistical methods; and qualitative data, by the Content Analysis Technique, outlined by Bardin. Results: the results demonstrate incipiency in the treatment of environmental issues. Regarding the theme, we highlight those that refer to socio-historical-cultural aspects in relation to the more direct environmental approach and facilitator of environmental conservation and consequent promotion of health. Final Considerations: The analysis allows identifying the fragility of the environmental approach in the analyzed programs, being necessary to improve the cross-sectionality of environmental issues.